Emerald ash borer intensifies harvest regimes on private land. Issue 2 (30th January 2022) - Holt, Jonathan R.; Smetzer, Jennifer R.; Borsuk, Mark E.; Laflower, Danelle; Orwig, David A.; Thompson, Jonathan R.
Abstract: Invasive forest insects have significant direct impacts on forest ecosystems and they are also generating new risks, uncertainties, and opportunities for forest landowners. The growing prevalence and inexorable spread of invasive insects across the United States, combined with the fact that the majority of the nation's forests are controlled by thousands of autonomous private landowners, raises an important question: To what extent will private landowners alter their harvest practices in response to insect invasions? Using a quasi‐experimental design, we conducted a causal analysis to investigate the influence of the highly impactful emerald ash borer (EAB) on (1) annual probability of harvest; (2) intensity of harvest; and (3) diameter of harvested trees, for both ash and non‐ash species on private land throughout the Midwest and mid‐Atlantic regions of the United States. We found that EAB detection had a negative impact on annual harvest probability and a positive impact on harvest intensity, resulting in a net increase in harvested biomass. Furthermore, our estimates suggest that EAB detection will influence private landowners to harvest greater quantities of ash, relative to non‐ash species. We also found that harvested trees in EAB‐infested areas had smaller diameters, on average, compared with those unaffected by EAB. These results can help policymakers, forest managers, and extension programs to anticipate and better advise landowners and managers about their options and the associated outcomes for forests.